Post-Tenure Pathways: Individualized Careers in Higher Education. Issue 1 (2nd January 2019) - Schmalz, Dorothy L.; Parr, Mary G.; Powell, Gwynn M.; Bricker, Kelly S.; Dustin, Daniel L.
Abstract: Promotion with tenure is often the ultimate goal for PhD students who choose to pursue a career in higher education. Extensive mentorship is provided for tenure-track faculty to smooth the path toward promotion with tenure, but most faculty members achieve this goal relatively early in their careers, leaving years if not decades ahead in a tenured position. Despite its advantages, tenured faculty report varying levels of satisfaction. For some, the post-tenure experience lives up to the expectations of freedom and achievement. For others, career goals post-tenure are elusive, and they experience a downturn in drive and motivation. Research indicates that inequities in responsibility and pay make women faculty more susceptible to post-tenure dissatisfaction than male faculty, and increased support and mentorship are among the most cited needs by post-tenure faculty. In this article, we present the details of the tenure contract that exists between faculty and universities and the unique pathways of three women faculty with the aim of presenting the diverse directions faculty can take in navigating a career in higher education.